Physical environment and violence perpetration among male youth in Pittsburgh: a spatial analysis. Issue 6 (12th July 2019) - Bushover, Brady; Miller, Elizabeth; Bair-Merritt, Megan; Abebe, Kaleab; Culyba, Alison
Abstract : Purpose: Examine associations between features of the built environment and violence perpetration among male youth. Methods: We enrolled 866 male adolescents, ages 13–19 years, as part of a violence prevention study in 20 lower-resource neighbourhoods in Pittsburgh, Pennsylvania, USA. Exposure to built environmental features was defined using participants' neighbourhood study site. Violence perpetration was measured by three survey items: physical fighting, threatening someone with a weapon, and injuring someone with a weapon. Logistic regression models examined associations between each environmental feature and violence perpetration. Results: Better neighbourhood walkability was associated with significantly lower odds of fighting (adjusted odds ratio (AOR)=0.86, 95% CI 0.76 to 0.99). Alcohol and tobacco outlets were associated with slightly lower odds of violence perpetration (AORs=0.89–0.96). Conclusions: This work extends previous studies from large urban centres to a mid-sized city context and suggests that walkable neighbourhoods create opportunities for social interactions and may serve as a protective factor in youth violence.